Computationally efficient modeling method of MMC based on arm equivalent time‐variant capacitance. (30th September 2018) - Li, Botong; Liu, Yichao; Li, Bin; Hong, Chao; Zhang, Ye; Yang, Jian
Summary: With the increase of the voltage as well as the capacity of the voltage source converter–based high voltage direct current (VSC‐HVDC) transmission system, it is difficult for the traditional modular multilevel converter (MMC) modeling method, which is based on the modeling of switching devices, to meet the demand for the simulation speed of the multiterminal transmission system. This paper proposed a computationally efficient modeling method of MMC by which the simulation speed is entirely unrelated to the number of the cascaded submodules. The paper is constructed as follows: The method for converting all the cascaded submodules in an arm into a single time‐variant capacitor was proposed first. Based on trapezoidal integration, the transient companion model of the equivalent time‐variant capacitor was studied. Then the efficient model of MMC is established based on arm equivalent time‐variant capacitor. Finally, the simulation accuracy and speed of the efficient model are verified in PSCAD/EMTDC.